Ragam Intervensi Olahraga untuk Menangani Gejala Vasomotor Wanita Klimakterium: Narrative Review - Hidayat, Nabila Nur fadilah; Sukmawati, Sukmawati; Witdiawati, Witdiawati (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Due to hormonal changes during menopause, various clinical symptoms arise in menopausal women including vasomotor symptoms. Exercise is one of the useful interventions to deal with vasomotor symptoms. However, clinical trials of the potential effectiveness of exercise interventions still require further research. The purpose of this narrative review is to identify and summarize the variety of exercise that can be used as an intervention and effective against vasomotor symptoms of climacterium women. The research design uses narrative review with SPIDER analysis techniques. The keywords in Indonesian are menopausal women AND exercise AND vasomotor symptoms and English menopause AND exercise AND vasomotor symptoms. The selection results obtained 6 articles from Finlandi, USA, Birmingham, Sweden and Tokyo for analysis. There are 3 types of exercise interventions to deal with vasomotor symptoms in climacterium women, namely aerobic exercise, resistance training and stretching. Resistance and stretching exercises are interventions that have proven effective and have a significant positive impact on decreasing the frequency and severity of vasomotor symptoms. Resistance and stretching exercises can be used as intervention options for vasomotor symptoms of female climacterium. Keywords: Climacterium Women, Exercise, Menopause, Vasomotor Symptoms  ABSTRAK Akibat perubahan hormonal masa menopause, timbul beragam gejala klinis pada wanita menopause diantaranya gejala vasomotor. Olahraga merupakan salah satu intervensi yang bermanfaat untuk menangani gejala vasomotor. Namun, secara uji klinis potensi keefektifan dari intervensi olahraga masih memerlukan penelitian lebih lanjut. Tujuan dari narrative review ini adalah untuk mengidentifikasi dan merangkum ragam olahraga yang dapat dijadikan intervensi serta efektif terhadap gejala vasomotor wanita klimakterium. Desain penelitian menggunakan narrative review dengan teknik analisis SPIDER. Kata kunci dalam bahasa Indonesia yaitu wanita menopause AND olahraga AND gejala vasomotor dan bahasa Inggris menopause AND exercise AND vasomotor symptoms. Hasil seleksi didapat 6 artikel yang berasal dari Finlandi, USA, Birmingham, Swedia dan Tokyo untuk dianalisis. Terdapat 3 ragam intervensi olahraga untuk menangani gejala vasomotor pada wanita klimakterium yakni olahraga aerobik, latihan ketahanan dan peregangan. Latihan ketahanan dan peregangan merupakan intervensi yang terbukti efektif dan memiliki dampak positif signifikan pada penurunan aspek frekuensi serta tingkat keparahan gejala vasomotor. Latihan ketahanan dan peregangan dapat dijadikan opsi intervensi terhadap gejala vasomotor wanita klimakterium. Kata Kunci: Wanita Klimakterium, Olahraga, Menopause, Gejala Vasomotor